2020
DOI: 10.33448/rsd-v9i10.7939
|View full text |Cite
|
Sign up to set email alerts
|

Abelha sem ferrão e seu potencial socioeconômico nos Estados da Paraíba e Rio Grande do Norte

Abstract: A meliponicultura exerce grande importância na agricultura familiar por ser fonte de renda para pequenos produtores. É uma atividade em expansão em todo território nacional pela vasta diversidade da flora e dos mais variados tipos de climas existentes no Brasil. Esse potencial produzido reflete na geração de renda do produtor e, com isso, se destaca como importante fator de inclusão social. Nos Estados da Paraíba e do Rio Grande do Norte, a criação racional de abelha sem ferrão é praticada de geração a geração… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
0
9
0
2
Order By: Relevance
“…Most participants (69.1%) reported raising bees less than five years ago, while 16.5% between five and ten years old, indicating that many beekeepers are beginners in the activity. In addition, it can be seen that 85.6% have been in the activity for less than ten years, which is approximately the time that the media and scientific research have been dedicated to showing the death and importance of bees (DANTAS et al 2020). Of the oldest beekeepers, 8.4% answered that they have been active between ten and 20 years and only 6% for more than 20 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most participants (69.1%) reported raising bees less than five years ago, while 16.5% between five and ten years old, indicating that many beekeepers are beginners in the activity. In addition, it can be seen that 85.6% have been in the activity for less than ten years, which is approximately the time that the media and scientific research have been dedicated to showing the death and importance of bees (DANTAS et al 2020). Of the oldest beekeepers, 8.4% answered that they have been active between ten and 20 years and only 6% for more than 20 years.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a portion of beekeepers may not be literate, or have basic literacy. Only 9% of illiterate or semi-literate Brazilians are users of this technology, with increasing use as the population's schooling increases (CETIC.BR 2018, DANTAS et al 2020. FELIX (2015), in its survey in the state of Ceará, observed that 13.55% of beekeepers were illiterate, 14.84% literate, 29.03% have incomplete elementary school, 7.74% complete elementary school, 5.16% incomplete high school, 20.65% complete high school, 7.10% complete higher education and 1.94% complete graduate education, with an average age group of 50.05 ± 15.30 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nota-se um valor bem abaixo se comprado com a venda de mel, o destaque fica para região Sudeste como a região que mais comercializa produtos apícolas (cera de abelha, geleia real e própolis), em segundo lugar a região Sul e em terceiro a região Nordeste. Os canais para a comercialização de produtos apícolas ainda são limitados, ainda a problemas com a inserção das tecnologias e com a questão da gestão rudimentar (Dantas et al, 2020). Porém, é consenso entre os pesquisadores e apicultores de que há espaço para crescer, e isso pode acontecer a partir do momento que as cooperativas e associações entenderem que é imprescindível uma gestão profissionalizada, o que vai permitir que ocorra a prospecção de compradores de maior envergadura e, proporcionará consequentemente um espaço favorável para que os produtores invistam mais em gestão e tecnologia, aumentando sua produção e qualidade do mel (Vidal, 2020;Silva et al, 2020).…”
Section: Fonte: Ibge (2017)unclassified
“…A Paraíba obteve produção de mel de 157 toneladas em 2017 e ocupou a 5ª posição de maior produtor entre os estados da região Nordeste (IBGE, 2017). Porém, alguns entraves como a inópia de cursos profissionalizantes e não aplicabilidade dos padrões de qualidade, acabam por dificultar a venda do mel no mercado externo e interno (Silva et al, 2020;Dantas et al, 2020).…”
Section: Exportação De Produtos Apícolasunclassified